Draft Annual Plan 1994-95 Part II Government of Maharashtra - Planning Commission (Planning Commission, 1994)
Economic services, Rural Development Irrigation and Flood Control Industry and Minerals Transport, Science, Technology and Environment Social Services General Services Special Area Programme.
Government of Maharashtra : Planning Department